2019
DOI: 10.1177/2397847319849521
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin abates induction of hepatic and renal oxidative damage, inflammation, and apoptosis in carbendazim-treated rats

Abstract: Exposure to the fungicide carbendazim (CBZ) has been associated with hepatorenal dysfunction. Quercetin, a naturally occurring polyphenolic phytochemical, reportedly possesses beneficial health effects. However, there is paucity of scientific information on the impact of quercetin on CBZ-induced hepatorenal damage. The present study investigated the protective mechanism of quercetin in CBZ-induced hepatic and renal damage in rats. The treatment groups consisted of control, CBZ alone (50 mg/kg), quercetin alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
2
10
0
1
Order By: Relevance
“…[26] Moreover, ALP is an index enzyme for hepatobiliary system integrity, [27] and high ALP serum levels indicate hepatobiliary damage. [28] Our results align with those of Owumi et al, [29] who confirmed that orally administered CBZ increased liver function biomarkers levels in rats. To some extent, our findings were also similar to those of Daundkar and Rampal, [30] who proved that CBZ could alter hepatorenal functions in male goats.…”
Section: Discussionsupporting
confidence: 90%
“…[26] Moreover, ALP is an index enzyme for hepatobiliary system integrity, [27] and high ALP serum levels indicate hepatobiliary damage. [28] Our results align with those of Owumi et al, [29] who confirmed that orally administered CBZ increased liver function biomarkers levels in rats. To some extent, our findings were also similar to those of Daundkar and Rampal, [30] who proved that CBZ could alter hepatorenal functions in male goats.…”
Section: Discussionsupporting
confidence: 90%
“…CBZ is extensively used as a biocide for the protection of product categories such as film, leather, rubber, fiber, polymerized materials, and building facades, according to European Union (EU) regulation number 528/2012 2 . CBZ is a huge global concern because it is frequently transferred via rains to areas where it poses harm to the environment, animal health, and human health 3 . The residual concentration of CBZ in farmland is about 0.18–1.74 mg/kg soil, while those in some fruits and vegetables were 0.37 and 0.60 mg/kg 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Our study found that carbendazim could induce a significant increase in the level of ROS values and a little increase in the level of SOD values. Oxidative stress caused by environmental pollution induces the increased expression of ROS and subsequently damages the antioxidant defense system [29]. SOD is responsible for the detoxification of toxic free radicals and their activities, which is used to evaluate the oxidative stress level and cellular antioxidant status [17,24].…”
Section: Discussionmentioning
confidence: 99%
“…SOD is responsible for the detoxification of toxic free radicals and their activities, which is used to evaluate the oxidative stress level and cellular antioxidant status [17,24]. Metalloenzyme SOD accelerates the transformation of endogenous cytotoxic superoxide radicals to H 2 O 2 , and the increase of SOD expression levels may contribute to improving the enzyme activities in order to eliminate the superoxide radicals induced by carbendazim and to prevent the occurrence of cellular dysfunction during exposure of carbendazim [24,29]. Higher exposure concentrations of carbendazim could cause severe oxidative stress, which subsequently destroys the balance of cell homeostasis and promote apoptosis [30].…”
Section: Discussionmentioning
confidence: 99%